UPAYA PENINGKATAN MOTIVASI BELAJAR SENI TARI PADA SISWA SMP MELALUI KEGIATAN APRESIASI SENI - Herlinah - (FBS UNY, 2006)
This research was aimed at improving learning motivation to danceand finding a learning model which is appropriate to State Junior High SchoolStudents in Yogyakarta.The steps of the research were adopted from a design model developedby Kemmis Mc.Taggart. It consists of four components, namely plan, action,observation and reflection, which form a chain in a cycle. The instruments of theresearch include class observation sheets, field notes and questionnaires. Themotivation improvement was measured through the learning process and result.The aspects measured in the learning process are attention, relevance,self-confidence and satisfaction. The learning result was evaluated through live artappreciation activities, which were also recorded in video. It was known that theroutine activities could increase the students’ learning motivation to dance.Key words: learning motivation, art appreciation